Efficacy of Psychosocial Interventions for Managing Anxiety and Depression in Cancer Patients: A Systematic Review of Randomized Controlled Trials - Dehnavi, Mahdie; Ghodsi, Hasan (Asian Pacific Journal of Cancer Nursing, 2025)
Objective: To systematically review and synthesize the current evidence from randomized controlled trials (RCTs) on the efficacy of psychosocial interventions for managing anxiety and depression in adult patients with cancer. Methods: A systematic search of electronic databases was conducted to identify relevant RCTs published from 2020 onwards. Studies that assessed the impact of a psychosocial intervention compared to a control condition on anxiety and/or depression outcomes in adult cancer patients were included. Two reviewers independently screened records, extracted data, and assessed the risk of bias using the Cochrane RoB 2 tool. Data on study characteristics, interventions, and outcomes were synthesized narratively. Results: Thirty-nine RCTs were included. The most frequently evaluated interventions were Cognitive Behavioral Therapy (CBT), mindfulness-based interventions (MBIs), and cognitive-behavioral stress management (CBSM). The majority of studies demonstrated that these interventions led to statistically significant reductions in symptoms of anxiety and depression compared to control conditions. CBT was the most consistently effective modality across diverse cultural settings. The analysis of intervention duration indicated that brief, structured programs (4-8 weeks) could be highly effective, while medium-term interventions (12-16 weeks) provided the most consistent evidence of efficacy. The overall body of evidence was deemed to be of reasonably high quality, with a low risk of bias in most included studies. Conclusion: Psychosocial interventions, particularly CBT, MBIs, and CBSM, are effective for reducing anxiety and depression in adult cancer patients. The findings support the integration of these interventions, including shorter, structured protocols, into standard oncology care to address the significant psychological burden of cancer. Future research should focus on personalizing interventions and optimizing their delivery for broader implementation.